Reproducibility of a battery of commonly used clinical tests to evaluate lumbopelvic motor control. Issue 4 (November 2015) - Habets, Bas; van Cingel, Robert E.H.; Ostelo, Raymond W.J.G.
Abstract: Objective: To determine reproducibility of a battery of clinical tests for evaluating lumbopelvic motor control (LMC). Design: Test-retest design. Participants: Fifty healthy subjects. Outcome Measures: Two raters independently examined performance on 12 clinical tests for evaluating LMC. All tests were scored on a seven-point scale, based on qualitative and quantitative performance. Subjects were measured twice, with a two week interval between examinations. Intra- and inter-rater reproducibility of each test were determined using intraclass correlation coefficients (ICCs), standard error of measurement, smallest detectable change (SDC) and limits of agreement. Results: Reliability of the tests ranged from poor to excellent. Intra-rater ICCs ranged from 0.00 to 0.82, whereas inter-rater ICCs varied from 0.00 to 0.96. SDC values were smallest for supine leg raising, bent knee fall out, prone bridge and unilateral prone bridge (<2 points). Conclusion: This study shows limited reproducibility of a battery of 12 clinical tests for the evaluation of LMC in a healthy population. Supine leg raising, bent knee fall out, prone bridge, and unilateral prone bridge showed the smallest measurement errors. The other 8 tests were found to have large measurement errors. Based on these results, dichotomization of the rating method might be considered in order to improve reproducibility values. Highlights: There is no generally accepted test for evaluating lumbopelvic motor control (LMC). This study investigated reproducibility of 12 commonly used clinical tests for the evaluation of LMC. Supine leg raising, bent knee fall out, prone bridge and unilateral prone bridge showed the smallest measurement error.